Gender-specific injury patterns in the lacrosse athlete - Cassandra Bakus; Conor Beil; Ashley J. Bassett; Meghan E. Bishop (Elsevier, 2022)
Introduction: Lacrosse is one of the fastest growing sports in the United States, increasing over 200% in the last 2 decades. With that increased participation, a corresponding rise in injury rates has also been identified, particularly impacting female lacrosse players. Objectives: The purpose of this study was to define the most common injury patterns seen in female lacrosse athletes and determine any gender specific risk factors that could contribute to injury risk and help develop prevention strategies. Methods: A literature search was performed in PubMed, the American Orthopaedic Society of Sports Medicine (AOSSM) journals and the USA Lacrosse 2022 Rules Book using the keywords "female lacrosse injuries", "lacrosse injuries", "injuries in female athletes". Results: The most common injuries seen in female lacrosse players are sprains/strains, concussions, contusions, and lacerations. The lower extremities are the most commonly injured body site. Female lacrosse players sustain a higher rate of sprains/strains, head, face, and eye injuries, hand/wrist fractures, and contusions compared to male lacrosse players, who unlike female lacrosse players are required to wear protective headgear and gloves. Conclusions: The differences in the style of play and the mandatory equipment requirements between men's and women's lacrosse may explain the discrepancy in injury rates between the sports. These differences may provide an opportunity to implement preventative strategies to better protect players and reduce risk of injury.